(untitled) - Blaunstein, Nathan (Hoboken, N.J., 2007)
Antennas and Propogation for Wireless Communication covers the basics of wireless communication system design with emphasis on antennas and propagation. It contains information on antenna fundamentals and the latest developments in smart antennas, as well as the radiation effects of hand-held devices. Antennas and Propogation for Wireless Communication provides a complete discussion of all the topics important to the design of wireless communication systems. Written by acknowledged authorities in their respective fields, the book deals with practical applications and presents real world examples. A solutions manual for college adopters accompanies the text. Ideal for engineers working in communication, antennas, and propagation for telecomm, military, and aerospace applications, as well as students of electrical engineering, this book covers all topics needed for a complete system design.
Keywords: Adaptive antennas,Radio wave propagation,Cell phone systems,Anten thích nghi,Sự lan truyền sóng vô tuyến,Hệ thống điện thoại di động; Equipment and supplies,Thiết bị và sự cung cấp